Gold-iron oxide (Au/Fe3O4) magnetic nanoparticles as the nanoplatform for binding of bioactive molecules through self-assembly - Lau, Elizabeth C. H. T.; Åhlén, Michelle; Cheung, Ocean; Ganin, Alexey Y.; Smith, David G. E.; Yiu, Humphrey H. P. (Frontiers in Molecular Biosciences, 2023)
Nanomedicine plays a crucial role in the development of next-generation therapies. The use of nanoparticles as drug delivery platforms has become a major area of research in nanotechnology. To be effective, these nanoparticles must interact with desired drug molecules and release them at targeted sites. The design of these "nanoplatforms" typically includes a functional core, an organic coating with functional groups for drug binding, and the drugs or bioactive molecules themselves. However, by exploiting the coordination chemistry between organic molecules and transition metal centers, the self-assembly of drugs onto the nanoplatform surfaces can bypass the need for an organic coating, simplifying the materials synthesis process. In this perspective, we use gold-iron oxide nanoplatforms as examples and outline the prospects and challenges of using self-assembly to prepare drug-nanoparticle constructs. Through a case study on the binding of insulin on Au-dotted Fe3O4 nanoparticles, we demonstrate how a self-assembly system can be developed. This method can also be adapted to other combinations of transition metals, with the potential for scaling up. Furthermore, the self-assembly method can also be considered as a greener alternative to traditional methods, reducing the use of chemicals and solvents. In light of the current climate of environmental awareness, this shift towards sustainability in the pharmaceutical industry would be welcomed.